Geophysical signatures of past and present hydration within a young oceanic core complex. Issue 4 (20th February 2014) - Blackman, Donna K.; Slagle, Angela; Guerin, Gilles; Harding, Alistair
Abstract Borehole logging at the Atlantis Massif oceanic core complex provides new information on the relationship between the physical properties and the lithospheric hydration of a slow‐spread intrusive crustal section. Integrated Ocean Drilling Program Hole U1309D penetrates 1.4 km into the footwall to an exposed detachment fault on the 1.2 Ma flank of the mid‐Atlantic Ridge, 30°N. Downhole variations in seismic velocity and resistivity show a strong correspondence to the degree of alteration, a recorder of past seawater circulation. Average velocity and resistivity are lower, and alteration is more pervasive above a fault around 750 m. Deeper, these properties have higher values except in heavily altered ultramafic zones that are several tens of meters thick. Present circulation inferred from temperature mimics this pattern: advective cooling persists above 750 m, but below, conductive cooling dominates except for small excursions within the ultramafic zones. These alteration‐related physical property signatures are probably a characteristic of gabbroic cores at oceanic core complexes.